Brains from non-Alzheimer’s individuals containing amyloid deposits accelerate Aβ deposition in vivo. - Duran-Aniotz, Claudia; Morales, Rodrigo; Moreno-González, Inés; Hu, Ping Ping; Soto, Claudio (BMC, 2013)
Background: One of the main features of Alzheimer’s disease (AD) is the presence of Aβ deposits, which accumulate in the brain years before the onset of symptoms. We and others have demonstrated that cerebral Aβ-amyloidosis can be induced in vivo by administration of AD-brain extracts into transgenic mice. However, it is currently unknown whether amyloid formation can be induced using extracts from individuals harboring Aβ deposits, but not clinical disease. Results: In this study we analyzed the amyloid-inducing capability of samples from individuals affected by mild cognitive impairment (MCI) and Non-Demented persons with Alzheimer’s disease Neuropathology (NDAN). Our results show that inoculation of transgenic mice with MCI and NDAN brain samples accelerated Aβ pathology in a similar way as extracts from confirmed AD. Conclusions: This data demonstrate that the sole presence of Aβ aggregates in a given sample, regardless of the clinical condition, is capable to accelerate Aβ deposition in vivo. These findings indicate that the amyloid-inducing activity may be present in the brain of people during pre-symptomatic or a-symptomatic stages of AD.
Keywords: Alzheimer, Enfermedad de; Modelos animales en investigación; Alzheimer